Portfolio guidance for veterinary nurses (Butterworth-Heinemann, 2003)
The Portfolio Guidance for Veterinary Nursing is an essential guide to the completion and submission of a successful veterinary nursing portfolio, which is a core component of the new S/NVQ Veterinary Nursing Qualification. It xplains the roles of the verifier and assessor, as well as the differences between assessment and verification and discusses the submission of the portfolio and provides an explanation of outcomes. It also includes examples of completed modules that will enable the student to present work of a high standard in the required format